If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4w + 12 + -2w = 72 + 3w + 3 Reorder the terms: 12 + -4w + -2w = 72 + 3w + 3 Combine like terms: -4w + -2w = -6w 12 + -6w = 72 + 3w + 3 Reorder the terms: 12 + -6w = 72 + 3 + 3w Combine like terms: 72 + 3 = 75 12 + -6w = 75 + 3w Solving 12 + -6w = 75 + 3w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-3w' to each side of the equation. 12 + -6w + -3w = 75 + 3w + -3w Combine like terms: -6w + -3w = -9w 12 + -9w = 75 + 3w + -3w Combine like terms: 3w + -3w = 0 12 + -9w = 75 + 0 12 + -9w = 75 Add '-12' to each side of the equation. 12 + -12 + -9w = 75 + -12 Combine like terms: 12 + -12 = 0 0 + -9w = 75 + -12 -9w = 75 + -12 Combine like terms: 75 + -12 = 63 -9w = 63 Divide each side by '-9'. w = -7 Simplifying w = -7
| 3x-7x-5=15 | | 15=t(30-4.9t) | | 4a-2=7+13 | | 11x-7=8x-28 | | 6x+12x+5y-6y= | | 12x*18y=4800 | | 5x^2-4xy-2x+y^2+2= | | (3w+4w)squared= | | -5x+77=4x-103 | | x^2+6x-22=-6 | | 5x^2+y^2-4xy-2x+5=0 | | a+10=7a | | 8x^2-34x=-30 | | (4n-1)=-6 | | 3w+4wsquared= | | zw+7x=c | | 5z+7z=17 | | 5y+6x=5 | | Y=5.0+.30X | | 7x+4=7(x+1) | | f(x)=x^3+5x^2+2x-8 | | 3b=8b-11 | | x^2+27x-198=0 | | 3(-x-2)=3x+6 | | -3v+5v=-16 | | 15y=45y-30 | | 5x+23=-x+5 | | 6(t-5)+6t=4(3t+4)-12 | | 9x+51y=26 | | 3xy=1+x | | 9c-2c= | | 7(6+4k)=-18+8k |